Colonização brasileira no Paraguai oriental: uma terrotorialidade brasiguaia - Gambetta, Luiz Carlos (2020)
This research shows the transformations of the Paraguayan border region, caused by the Brazilian immigrants between 1950 and 1990, their social, economic, political and demographic effects. It is analysed the formation of Brazilian territorialities, under a geopolitical approach, related to the territorial disputes and the formation of the borders between Brazil and Paraguay, in the colonial, imperial and republican context and that, in some way, influenced the formation of “Braziguayan” space. The history of the colonization of a vast territory is reconstructed to understand the formation of the cities and the consequences derived from the pioneering. The hypotheses of the work are based on the analysis of the socioeconomic and territorial history of Paraguay, where answers are found to explain why the country had to seek in the Brazilians people the solution to colonize frontier areas, which resulted in the modernization of the main sector of its economy, however, on the other hand, definitively attracted to the geopolitical orbit of Brazil.